2006
DOI: 10.1158/1078-0432.ccr-05-1347
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Hepatoma-Derived Growth Factor Is Correlated with Lymph Node Metastasis and Prognosis of Gastric Carcinoma

Abstract: Purpose: Hepatoma-derived growth factor (HDGF) is a unique nuclear/growth factor and might play an important role in the development and progression of carcinomas. In the present study, association of HDGF expression with recurrence and prognosis of gastric carcinoma was examined. Patients and Methods: HDGF expression in 317 patients with gastric carcinoma (233 males and 84 females) with ages ranging from 26 to 81years (median, 60 years) was analyzed by immunohistochemistry. Samples with >90% of tumor cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 22 publications
3
85
0
Order By: Relevance
“…The following articles were also excluded: three duplicated publications (Zhou et al, 2007b;Zhou et al, 2010a;Yang et al, 2014); three without data for HR and 95%CI calculations and adequate contact with the investigators could not be established (Natrajan et al, 2006;Mao et al, 2008;Hanada et al, 2013); two with a sample size<50 (Hsu et al, 2012;Tao et al, 2014); two in which HDGF expression was not detected by IHC methods (Savola et al, 2009;Zhang et al, 2010); three uncorrelated. Finally, 26 cohort studies were found eligible for the meta-analysis (Hu et al, 2003;Ren et al, 2004;Iwasaki et al, 2005;Uyama et al, 2006;Yamamoto et al, 2006;Yoshida et al, 2006;Chang et al, 2007;Yamamoto et al, 2007;Zhou et al, 2007a;Hu et al, 2009;Zhou et al, 2010b;Liu et al, 2011;Wang et al, 2011;Zhang et al, 2011;Chen et al, 2012a;Chen et al, 2012b;Lin et al, 2012;Han et al, 2013;Li et al, 2013a;Li et al, 2013b;Li et al, 2013c;Yang et al, 2013;Guo et al, 2014b;Song et al, 2014;Wang et al, 2014;Zhang et al, 2014), containing 32 datasets (29 datasets for OS; 17 datasets for DFS) were qualified to the standard of the meta-analysis. The main characteristics of the selected studies were summari...…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following articles were also excluded: three duplicated publications (Zhou et al, 2007b;Zhou et al, 2010a;Yang et al, 2014); three without data for HR and 95%CI calculations and adequate contact with the investigators could not be established (Natrajan et al, 2006;Mao et al, 2008;Hanada et al, 2013); two with a sample size<50 (Hsu et al, 2012;Tao et al, 2014); two in which HDGF expression was not detected by IHC methods (Savola et al, 2009;Zhang et al, 2010); three uncorrelated. Finally, 26 cohort studies were found eligible for the meta-analysis (Hu et al, 2003;Ren et al, 2004;Iwasaki et al, 2005;Uyama et al, 2006;Yamamoto et al, 2006;Yoshida et al, 2006;Chang et al, 2007;Yamamoto et al, 2007;Zhou et al, 2007a;Hu et al, 2009;Zhou et al, 2010b;Liu et al, 2011;Wang et al, 2011;Zhang et al, 2011;Chen et al, 2012a;Chen et al, 2012b;Lin et al, 2012;Han et al, 2013;Li et al, 2013a;Li et al, 2013b;Li et al, 2013c;Yang et al, 2013;Guo et al, 2014b;Song et al, 2014;Wang et al, 2014;Zhang et al, 2014), containing 32 datasets (29 datasets for OS; 17 datasets for DFS) were qualified to the standard of the meta-analysis. The main characteristics of the selected studies were summari...…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
“…In recent years, elevated levels of hepatoma-derived growth factor (HDGF) have been observed in a variety of malignancies and high levels of HDGF appears to be associated with increased malignancy across cancers, as witnessed by the correlation with adverse characteristics such as poor patient survival (Hu et al, 2003;Ren et al, 2004;Iwasaki et al, 2005;Uyama et al, 2006;Yamamoto et al, 2006;Yoshida et al, 2006;Chang et al, 2007;Yamamoto et al, 2007;Zhou et al, 2007a;Hu et al, 2009;Savola et al, 2009;Zhang et al, 2010;Zhou et al, 2010b;Liu et al, 2011;Wang et al, 2011;Ye et al, 2011;Zhang et al, 2011;Chen et al, 2012a;Chen et al, 2012b;Hsu et al, 2012;Lin et al, 2012;Han et al, 2013;Hanada et al, 2013;Li et al, 2013a;Li et al, 2013b;Li et al, 2013c;Yang et al, 2013;Guo et al, 2014b;Song et al, 2014;Wang et al, 2014;Yang et al, 2014;Zhang et al, 2014). As a multifunctional protein Bao et al, 2014) widely expressed by many types of human cells, HDGF is involved in the regulations of a myriad of cancer cell activities during cancer transformation (Yang et al, 2013), apoptosis , angiogenesis (Ren et al, 2009), and metastasis (Chen et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…71 Similarly, HDGF is overexpressed in many different cancers, including gastrointestinal stromal tumors (GISTs), 72 esophageal carcinoma, 73 pancreatic cancer, 74 hepatocellular carcinoma, 75 non-small cell lung cancer, 76 colorectal cancer 77 and melanoma, 78 and has potent angiogenic, 79 invasive 80 and metastatic potential. 73 Contrasting its role under pathophysiological conditions, such as gliomagenesis, necrosis can also be beneficial for an organism as it constitutes a warning system against toxic exposure. Low toxic insults may incite apoptotic cell death, resulting in cellular shrinkage, formation of apoptotic bodies and efficient engulfment of apoptotic remnants by phagocytes.…”
Section: The Two Faces Of Necrosis-a Benefical Adaptive Warning Systementioning
confidence: 99%
“…Some research suggests that HDGF is involved in aggressive tumor behaviors such as progression, angiogenesis, metastasis and recurrence (11,(19)(20)(21). We previously found that HDGF was overexpressed in glioma tissues and that the more advanced the stage, the higher the expression level of HDGF (14).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating clinical evidence demonstrates that HDGF expression is correlated with increased malignancy of different types of tumors and that it could be an independent prognostic factor in a variety of human cancers (10)(11)(12)(13). We recently found that HDGF is overexpressed in glioma specimens, and its expression level may correlate with the clinical pathological grade (14).…”
Section: Introductionmentioning
confidence: 98%